2010
DOI: 10.1177/1934578x1000500717
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins from Seseli hartvigii

Abstract: ]psoralen (1) were first isolated from whole plants of Seseli hartvigii together with one new natural product 6-(3'-methyl-2'-oxo-3'-butenyl)-7-methoxycoumarin (2), and four known compounds (tamarin, bergaptol, notoptol, and a mixture of β-sitosterol and stigmasterol). The structure of 1 was elucidated by extensive spectroscopic analysis and chemical conversion. The modified Mosher's method and HPLC were applied to determine its stereochemistry. Both Rand S-configurations exist in 1; after modification by Mosh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Besides, the genus Seseli is known to be rich in coumarins, a number of which are recognized for their medicinal properties [12][13][14][15]. Attempts were also made to explore the detailed underlying mechanism of coumarins isolated from Seseli species, as active pharmacological agents.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the genus Seseli is known to be rich in coumarins, a number of which are recognized for their medicinal properties [12][13][14][15]. Attempts were also made to explore the detailed underlying mechanism of coumarins isolated from Seseli species, as active pharmacological agents.…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, there are limited studies on Seseli species based on the coumarins Tosun, 2006;Tosun et al, 2006a, Zhang et al, 2010Shehzad et al, 2013) and the essential oils (Baser et al, 2000;Kaya et al, 2003;2006b;2006c). Previously, antimicrobial (Tosun et al, 2004), anti-inflammatory and antinociceptive (Küpeli et al, 2005;Tosun et al, 2009;Chun et al, 2016) effects have been performed on Turkish Seseli species.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of previously conducted chemical studies, it is known that Seseli species are a source of coumarins, sesquiterpenes, and phenyl propanoides. 5-9 Previous analyses of the essential oils from various Seseli species demonstrated that the main components are quite different from species to species: sabinene, α-pinene, and β-phellandrene in S. globiferum aerial parts 10 ; α-pinene in S. rigidum Waldst. & Kit.…”
mentioning
confidence: 99%